Quantifying the biodiversity values of reforestation: perspectives, design issues and outcomes in Australian rainforest landscapes - Catterrall, C.; Kanowski, J.; Wardell-Johnson, Grant; Proctor, H.; Rels, T.; Harrison, D.; Tucker, N. (Royal Zoological Society of New South Wales, 2004)
Following two centuries of land clearing, the past two decades have seen growing efforts to re-establish forest on formerly-cleared sites. While the immediate goals of reforestation vary, there is also a widespread expectation that one of its effects will be an improvement in "biodiversity value". However, agreed standards concerning how this can be measured, and against what benchmarks it should be judged, are lacking. This paper describes a study of biodiversity development in different types of rainforest reforestation in tropical and subtropical eastern Australia. It provides information on the responses of rainforest fauna and also discusses key issues of survey design and methodology that, if ignored, may limit the effectiveness of monitoring programs.The nature of rainforest, its history within Australia, and its role as fauna habitat are briefly reviewed. Modern deforestation and human land use, and various reforestation pathways (including regrowth, timber plantation, and ecological restoration projects) are described. Then design principles, biodiversity measurements, and issues relating to their choice are discussed.These include: spatial scale; site selection and replication in relation to environmental variation; reference sites; the array of potentially measurable biotic and process variables, and spatio-temporal measurement scales. Finally we explore analytical options and present selected findings, using univariate and multivariate approaches, and comparing simple species richness, functional groupings, and analyses of taxonomic composition. Rainforest biodiversity value is defined as the development of a rainforest-like set of biota and ecological processes. Reforested sites were generally intermediate between pasture and rainforest reference sites in the measured components of rainforest biodiversity value. Many components had been rapidly (by around 10 years) acquired by ecological restoration sites, although it is clear that some components will take decades or longer to develop. The results also show: (1) the existence of production/ biodiversity trade-offs, in that sites managed for timber production acquired less biodiversity value than those planted for ecological restoration; (2) moderate correspondence across different indicator taxa when they are analysed as functional groups; (3) very little agreement among indicator taxa when overall richness is used; (4) a likelihood of important landscape and context effects. Long-term conservation of rainforest fauna will require rainforest restoration over substantial areas of currently denuded land. However, although rainforest restoration may often show reasonable success, it should not be viewed as an alternative to conserving existing remnants and advanced regrowth.